Cronache di vita universitaria ai tempi del CoViD-19. Catalogo del Contest fotografico Premio CUG Università Federico II, 2020-21 - Galgano, Francesca (Cultura delle differenze: Diritto, conoscenza, formazione, 2021)
The Committee for Equal Opportunities, Well-being at Work and against Discriminations of the University Federico II stages an annual photographic contest addressed to its scholars, students and employees. This catalogue collects all the pictures sent and the motivations of the award by Jury: every picture contains a tale about academic life (and not only) during the past two years, in so evocative way as only images can do.